2015
DOI: 10.3390/e17010231
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Entropy Analysis of Heart Rate Variability for Assessing the Severity of Sleep Disordered Breathing

Abstract: Obstructive sleep apnea (OSA) is an independent cardiovascular risk factor to which autonomic nervous dysfunction has been reported to be an important contributor. Ninety subjects recruited from the sleep center of a single medical center were divided into four groups: normal snoring subjects without OSA (apnea hypopnea index, AHI < 5, n = 11), mild OSA (5 ≤ AHI < 15, n = 10), moderate OSA (15 ≤ AHI < 30, n = 24), and severe OSA (AHI ≥ 30, n = 45). Demographic (i.e., age, gender), anthropometric (i.e., body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
(48 reference statements)
3
18
0
1
Order By: Relevance
“…Some studies have suggested that certain nonlinear measures of HRV are better predictors of future adverse events in various patient groups than the standard linear measures [13]. For example, Gutiérrez-Tobal et al proved the usefulness of the spectral entropy and multiscale entropy analyses of HRV to detect OSA [6], and Pan et al showed that multiscale entropy analysis may serve as a preliminary screening tool for assessing OSA severity prior to polysomnography [15]. Al-Angari et al applied sample entropy to the analysis of HRV complexity in subjects with and without OSA [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that certain nonlinear measures of HRV are better predictors of future adverse events in various patient groups than the standard linear measures [13]. For example, Gutiérrez-Tobal et al proved the usefulness of the spectral entropy and multiscale entropy analyses of HRV to detect OSA [6], and Pan et al showed that multiscale entropy analysis may serve as a preliminary screening tool for assessing OSA severity prior to polysomnography [15]. Al-Angari et al applied sample entropy to the analysis of HRV complexity in subjects with and without OSA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that OSA affects the normal variation of heart rate and that both HRV [5,7,15,31] and PRV [9,32] might help identifying OSA events. Some studies have suggested that certain nonlinear measures of HRV are better predictors of future adverse events in various patient groups than the standard linear measures [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study analyzed trajectories and EMG signals by dividing the multiscale entropy index (MEI) into four small scale intervals using the MSFuzzyEn approach for comparison [30]:…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…Because time-series data of the GM morphology are inherently complex, chaos and nonlinear dynamics analyses of these time-series data are therefore suitable mathematical techniques for extracting their informative statistical properties. Moreover, chaos and nonlinear dynamics have been increasingly reported as effective computational methods for analyzing complex data in medicine and biology [30][31][32][33][34][35][36]. We therefore explore several methods of chaos and nonlinear dynamics to extract features from time-series data of the GM spatial structure of the brain on MRI.…”
Section: Introductionmentioning
confidence: 99%